Being an older person: modulation of walking speed with geriatric walking motion avatars - Koseki, Yusuke; Amemiya, Tomohiro (Frontiers in Virtual Reality, 2024)
The phenomenon of one's walking speed being affected by that of other pedestrians on the street is often observed in real-world scenarios. However, the effects of the motion and familiarity of avatars on a user in virtual reality have not been thoroughly investigated. Therefore, this study explored how alterations in human avatars affect the walking speed and sensation of users. Furthermore, walking speed has been shown to be influenced not only by visual perception but also by cognition. However, few studies have investigated the relationships between visual perception, cognition, and behavior. Therefore, we examined the relationships between stereotypical words for older people, a representative example of cognition-induced changes in walking speed, and visual perception stimuli of avatars. The results revealed a significant interaction between the stereotype and avatar walking motion. In particular, in the absence of the stereotype, participants were strongly affected by the older walking motion of the avatar, and their walking speed decreased. We also found that the walking motion of avatars significantly affects participants walking speed and sensation. These findings provide pioneering insights into the psychological factors that regulate human walking speed and propose a new method for manipulating the user's walking speed and sensation in VR space.